2021
DOI: 10.1021/acsabm.1c00320
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon-Assisted Fluorescence Enhancing and Quenching: From Theory to Application

Abstract: The integration of surface plasmon resonance and fluorescence yields a multiaspect improvement in surface fluorescence sensing and imaging, leading to a paradigm shift of surface plasmonassisted fluorescence techniques, for example, surface plasmon enhanced field fluorescence spectroscopy, surface plasmon coupled emission (SPCE), and SPCE imaging. This Review aims to characterize the unique optical property with a common physical interpretation and diverse surface architecture-based measurements. The fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 191 publications
0
26
0
Order By: Relevance
“…[ 7b ] Plasmonic nanostructures have emerged as promising functional materials in fundamental and technologically relevant studies of optical, electronic, and optoelectronic devices, whose unique properties are enabled by localized surface plasmons. [ 5l,8 ] Early experiments have shown that plasmonic nanoantennas are able to promote both absorption and emission of single molecules under high‐power light excitation (such as 2.4 kW cm −2 ) through producing highly localized electromagnetic near‐field enhancement and the Purcell effect, leading to high‐brightness fluorophore blinking. [ 9 ] However, it has remained challenging to realize fluorophore blinking through low‐power light excitation, for instance, by a mercury lamp, simply because its excitation power density (typically on the order of 1 W cm −2 ) is too low to achieve sufficient photon emissions from single molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7b ] Plasmonic nanostructures have emerged as promising functional materials in fundamental and technologically relevant studies of optical, electronic, and optoelectronic devices, whose unique properties are enabled by localized surface plasmons. [ 5l,8 ] Early experiments have shown that plasmonic nanoantennas are able to promote both absorption and emission of single molecules under high‐power light excitation (such as 2.4 kW cm −2 ) through producing highly localized electromagnetic near‐field enhancement and the Purcell effect, leading to high‐brightness fluorophore blinking. [ 9 ] However, it has remained challenging to realize fluorophore blinking through low‐power light excitation, for instance, by a mercury lamp, simply because its excitation power density (typically on the order of 1 W cm −2 ) is too low to achieve sufficient photon emissions from single molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study, Min et al explored long-range (> 100 nm) SPR-enhanced fluorescence on a periodic array instead of the localized "hotspot" surfaces (< 20 nm). This approach is more suitable for measurements with intact EVs given their dimension (30-1000 nm) [118,119]. Four fluorescent dyes (AF488, Cy3, Cy5, and Cy5.5) were conjugated with streptavidin separately in order to code biotinylated EV membrane proteins (CD9, CD63, CD81, GAPDH, EGFR, EGFRvIII) after their capture on neutravidin-PEG layers (Fig.…”
Section: Spr Arraysmentioning
confidence: 99%
“…Plasmonic and photonic substrates are being increasingly employed to improve fluorescence properties in multiple ways. 1–7 Useful control over fluorescence emission has been accomplished by integrating fluorophores with thin metal films of silver or gold that support surface plasmon oscillations, and hybrid metal–dielectric configurations that support both plasmonic and optical waveguide modes. 8–12 In these structures, fluorophores placed within near-field distances of the metal surface can create and couple with surface plasmons (and/or waveguide modes), and subsequently radiate through the substrate with narrow angular distribution.…”
Section: Introductionmentioning
confidence: 99%
“…17–22 To improve the scope of SPCE and benefit from the surface plasmon field enhancement, a number of studies are being carried out to engineer the spacer layer between the metal and the fluorophore with the help of different materials like polymers, silicon, protein/DNA, carbon nanotubes and graphene. 1,22–24 However, the expansion of SPCE for practical applications is still hindered by the metallic component, which is typically limited to the conventional plasmonic materials, silver and gold.…”
Section: Introductionmentioning
confidence: 99%